‘God is always on my side’: internal and external predictors of workplace bullying targets’ help-seeking behavior in a religious context - Deikus, Mykolas; Vveinhardt, Jolita (Frontiers in Psychology, 2024)
Workplace bullying is a pervasive issue that affects millions of individuals worldwide, leading to severe psychological and social consequences. This study examines the factors influencing the decisions of religious individuals who have experienced workplace bullying, with an explicit focus on their choice to seek help from their religious community. The study involved respondents from various religious groups, most of whom were Roman Catholic. The research employs a crosssectional design, integrating quantitative analysis with qualitative insights. Data from 1231 respondents were analysed via descriptive statistics, correlation, regression, and content analysis methods. The main coping strategies identified were self-coping and seeking help within a close, trusted environment. Attitudes towards the religious organization (subjective norms) consistently predicted help-seeking decisions more accurately than access to religious counselling (perceived behavioral control) or personal values. This research provides one of the first empirical insights into how religious communities can actively mitigate the psychological impact of workplace bullying, offering a novel perspective on the intersection of faith and mental health. The findings suggest that religious organizations could be crucial in supporting victims by enhancing outreach and counselling services, contributing to a holistic approach to workplace well-being. These findings have significant implications for religious communities, highlighting their potential to support their members in times of active distress.